Análise numérica e experimental de estruturas de guarda-corpos para a segurança do trabalho na construção civil - Baruffi, Diniane (2017)
Edge protection systems are used to prevent accidents caused by work at height in building construction. The importance of the occupational safety and its influence on costs and social damage caused by accidents in civil construction, justify measures to create effective preventionsystems. This subject continues to demand attention from the civil construction industry and from government, due to the increasingly occurrence of work accidents by fall from heights in buildings and infrastructure construction. In the field of guardrail structures used with this purpose, in Brazil the regulation NR-18, NR-35 and RTP 01 deal with it, however few is defined about the analysis and design of those systems. Some international standards, on the other hand, define some criteria beyond those used by Brazilian standards, especially about structural design. It´s observed that loads are different in the all consulted standards. In this research, it is compared the literally results specialized to the analysis with structures used to this purpose, using materials such as wood and steel and evaluating the results. To achieve these goals, numeric modellings were made through static analysis and explicit dynamic analysis using the Finite Element Method (FEM) simulating and analyzing the impact generated by a solid like human body and static loads, according to the standards in simplified guardrail models typically used for work safety. For the numerical models validation, it was made experimental tests, applying static charges and with impact in the structures. The numerical and experimental results obtained in the research shows that the structures are able to support and absorb the charges applied. However, it is necessary to develop a new specific test for these structures since the Brazilian regulation NBR 4718 (ABNT, 2018a), for definitive guardrails, were restricted and for this reason the structures are not able to attend some maximum values for displacement in some cases. Though, it is considered that the charges of 150 kgf/m for an impact test, required by MTE, is more efficient than one with 77kg and distant 20,38cm. Indeed, during numerical and experimental tests and static analysis of impact, it was no local or global rupture of the system.